KEJADIAN STAGNANT DAN STOCKOUT OBAT KARDIOVASKULER DI INSTALASI FARMASI RUMAH SAKIT - Eleonora Maryeta Toyo; Sri Suwarni; Yolanda Ernidiasanti (Jurnal Farmasi & Sains Indonesia, 2021)
Drug management is carried out as an effort to control drug inventory in hospital pharmacy installations to know the incidence of stagnant and stockout of cardiovascular drugs from the internal medicine specialist poly. This research was conducted in March-April 2021, with a cross-sectional study design with retrospective data search. The data instrument used is an electronic stock card specifically for the use of cardiovascular drugs in hospital outpatient installations, including; antianginal, antidyslipidemic, antihypertensive, and antiplatelet drugs. The number of samples used was 50 items of cardiovascular drugs. Data processing is carried out qualitatively and quantitatively. The results showed that the highest number was found in the antihypertensive therapy class as many as 32 items with an amount of stagnant 12% and a total stockout of 31.3%. Keywords: Cardiovascular Medicine, Stagnant, Stockout, Hospital